2018
DOI: 10.1080/17453674.2018.1439238
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between modified Dunn procedure and in situ fixation for severe stable slipped capital femoral epiphysis

Abstract: Background and purposeThe best treatment option for severe slipped capital femoral epiphysis (SCFE) is still controversial. We compared clinical and radiographic outcomes of modified Dunn procedure (D) and in situ fixation (S) in severe SCFE.Patients and methodsWe retrospectively compared D and S, used for severe stable SCFE (posterior sloping angle (PSA) > 50°) in 29 patients (15 D; 14 S). Propensity analysis and inverse probability of treatment weights (IPTW) to adjust for baseline differences were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…In our study, the mean preoperative Southwick angle was 59.1° (range, 50.6° to 75°). This finding was comparable with the results of other studies: Novais et al[ 14 ] observed the aforementioned angle as 65° (range, 54° to 81°), Trisolino et al[ 17 ] calculated it as 68°±11°, and Guindani et al[ 16 ] found it as 70° (range, 60° to 90°). In the current study, we demonstrated that the mean postoperative Southwick angle improved to -0.8°.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our study, the mean preoperative Southwick angle was 59.1° (range, 50.6° to 75°). This finding was comparable with the results of other studies: Novais et al[ 14 ] observed the aforementioned angle as 65° (range, 54° to 81°), Trisolino et al[ 17 ] calculated it as 68°±11°, and Guindani et al[ 16 ] found it as 70° (range, 60° to 90°). In the current study, we demonstrated that the mean postoperative Southwick angle improved to -0.8°.…”
Section: Discussionsupporting
confidence: 90%
“…Guindani et al[ 16 ] conducted a single-center study and evaluated the three- year follow-up clinical and radiological outcomes of 23 hips with severe SCFE treated with MDO technique. Moreover, Trisolino et al[ 17 ] compared the two techniques only in severe slips and the number of patients treated with MDO was 15. With a large sample size of 28 patients, Madan et al[ 18 ] investigated the results of MDO technique in severe slips including acute cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Main analyses were performed by applying regression models on observations with complete data (complete-case analysis approach). In addition, the results’ consistency was evaluated by adjusting the comparison between the two populations by applying different propensity score approaches [ 29 ]. A p -value < 0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%